2012
DOI: 10.1155/2012/461468
|View full text |Cite
|
Sign up to set email alerts
|

Nanoenhanced Materials for Reclamation of Mine Lands and Other Degraded Soils: A Review

Abstract: Successful mine soil reclamation facilitates ecosystem recovery, minimizes adverse environmental impacts, creates additional lands for agricultural or forestry uses, and enhances the carbon (C) sequestration. Nanoparticles with extremely high reactivity and deliverability can be applied as amendments to improve soil quality, mitigate soil contaminations, ensure safe land–application of the conventional amendment materials (e.g., manures and biosolids), and enhance soil erosion control. However, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 151 publications
(209 reference statements)
1
26
0
Order By: Relevance
“…Combined with biological methods (e.g., re-vegetation of mine wastelands), application of chelates increases metal solubility in soils, overcomes the diffusional limitation of metals in the rhizosphere, and facilitates root-to-shoot translocation of the metal (McGrath et al 2001). Recently, application of nanoparticles has emerged as a novel technology for restoration of mine wastelands owing to their large specific surface area, reactivity, and deliverability (Liu and Lal 2012). These authors also noted that zeolites, zero-valent iron nanoparticles, iron oxide nanoparticles, phosphate-based …”
Section: Chemical Methodsmentioning
confidence: 99%
“…Combined with biological methods (e.g., re-vegetation of mine wastelands), application of chelates increases metal solubility in soils, overcomes the diffusional limitation of metals in the rhizosphere, and facilitates root-to-shoot translocation of the metal (McGrath et al 2001). Recently, application of nanoparticles has emerged as a novel technology for restoration of mine wastelands owing to their large specific surface area, reactivity, and deliverability (Liu and Lal 2012). These authors also noted that zeolites, zero-valent iron nanoparticles, iron oxide nanoparticles, phosphate-based …”
Section: Chemical Methodsmentioning
confidence: 99%
“…Nanomaterials have a higher reactivity and greater adsorption ability, and some studies have suggested that nanomaterials are superior to traditional amendments using common particle sizes for soil remediation [15]. Theoretically, in this study, compared to mHAP, nHAP would immobilize a larger amount of Pb, Cd, and Zn, likely due to its smaller particle size and larger surface area.…”
Section: Effects Of Amendments On Pakchoi Biomassmentioning
confidence: 77%
“…Among these amendments, hydroxyapatite is considered one of the most effective natural materials in immobilizing heavy metals in soil [11,12]. With the rapid development of nanotechnology, nanoparticles of hydroxyapatite has been effectively applied to immobilize and remediate toxic heavy metals in soil [13][14][15]. However, until now little research has been done comparing the effect of nano-and micro-hydroxyapatite (nHAP and mHAP) in remediating heavy metals-contaminated soils.…”
mentioning
confidence: 99%
“…Some of the emerging strategies towards the reclamation of AMLs are the use of transgenic plants for the removal of toxins from AMLs (Seth 2012), thereby mitigating its risk followed by the use of nanomaterials as amendments for abandoned mine soil reclamation (Liu and Lal 2012). Though these approaches are at their developing stage, still several studies are warranted in the future to confirm their field-scale adaptability in the reclamation of AMLs.…”
Section: Emerging Reclamation Approaches For Amlsmentioning
confidence: 99%